2017
DOI: 10.1093/geront/gnx041
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Physical Environment on Depressive Symptoms of Older Residents Living in Care Homes: A Mixed Methods Study

Abstract: We provide new evidence to suggest that access to outdoor space predicts depressive symptoms in older people living in care home. Interventions aimed at increasing access to outdoor spaces could positively affect depressive symptoms in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…Care home residents place a high value on outdoor spaces being accessible, with the need to be around greenery of particular importance (Kearney & Winterbottom, 2008). Lack of access to outdoor spaces has also been reported as the main environmental variable predicting depressive symptoms in care home residents (Potter et al, 2018). Despite this, there are several barriers such as physical limitations, lack of assistance and design issues that can prevent care home residents from enjoying the outdoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Care home residents place a high value on outdoor spaces being accessible, with the need to be around greenery of particular importance (Kearney & Winterbottom, 2008). Lack of access to outdoor spaces has also been reported as the main environmental variable predicting depressive symptoms in care home residents (Potter et al, 2018). Despite this, there are several barriers such as physical limitations, lack of assistance and design issues that can prevent care home residents from enjoying the outdoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies show that a good fit between the elderly and their home environments has significant effects on healthy aging (Iwarsson 2005). The goal in good design for the elderly is supporting their functional and cognitive abilities (Potter et al 2018). Satisfaction with housing environments is also an important factor in mental and psychological health (Oswald et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently going outdoors may increase the QoL of residents through interaction with nature, the activities undertaken whilst outside, such as walking or other physical activities, or possibly by elevating vitamin D [2,[23][24][25][26]. For people living with dementia in residential aged care in the UK, restricted access to outdoor areas has been associated with depressive symptoms [7], but only a relatively short duration of outdoor exposure may be needed to show an association with improved mood [9]. Residents of care facilities frequently have low serum vitamin D which has been associated with depression, so increased time spent outdoors may improve mood by increasing vitamin D [23,27].…”
Section: Discussionmentioning
confidence: 99%
“…Even if facilities offer independent access to outdoor spaces there may be barriers to the residents using these areas, explaining the lack of benefit on quality of life. Whilst dependencies due to physical health and mobility issues are possible barriers [5,7], this analysis has adjusted for differences in function and cognition between the residents. A recent systematic review has found that key barriers and enablers relate to the design of outdoor areas and the main building in terms of providing doors that are easy to open and close access points, weather (which can be addressed in part by providing adequate and appropriate shade, shelter and clothing), staffing factors and provision of social activities outdoors [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation